Decoding joint complaints in children: a diagnostic approach to rheumatic and non-rheumatic disorders - İvedi, Hatice and Balcı, Sibel and Bayrak, Yunus Emre and Öksel, Ali and Şahin, Nihal and Sönmez, Hafize Emine (The Turkish Journal of Pediatrics, 2026)
Introduction. Musculoskeletal (MSK) complaints are common in children, with many cases ranging from benign to serious conditions. While these patients are often referred to pediatric rheumatologists, only about half are diagnosed with rheumatic diseases. The objective of this study is to identify key clues that assist in the differential diagnosis of patients presenting with joint complaints at pediatric rheumatology outpatient clinic. Material Methods. In this one-year study, patients with joint pain were assessed using a standardized form. Demographic, clinical, and examination data were collected and anonymized. Initial assessments were done by pediatric rheumatology fellows or residents, with final diagnoses confirmed by a pediatric rheumatologist. Results. This study included 414 patients aged 0-18 years with joint pain, of whom 273 were diagnosed with rheumatologic conditions and 141 with non-rheumatologic conditions. Patients with rheumatologic conditions had significantly higher laboratory values, including leukocyte counts, neutrophils, platelets, C-reactive protein, and erythrocyte sedimentation rate, all with p < 0.001. Multivariable analysis revealed that arthritis (adjusted odds ratio [aOR] 2.63, 95% confidence interval [CI] 1.09-6.33) and rash (aOR 4.37, 95% CI 1.38-13.86) predicted rheumatic disease in acute presentations, while in chronic complaints arthritis (aOR 2.61, 95% CI 1.30-5.21), morning stiffness (aOR 3.47, 95% CI 1.69-7.11), migratory pain (aOR 3.45, 95% CI 1.01-11.80), and fever (aOR 12.89, 95% CI 4.41-37.68) were independent predictors, whereas myalgia was associated with non-rheumatic conditions (aOR 0.35, 95% CI 0.15-0.83). Conclusion. In conclusion, this study emphasized the importance of clinical clues in diagnosing rheumatic diseases in children with joint pain. An accurate diagnosis depends on a thorough history and physical examination. Improving the differential diagnosis of joint pain is essential to reduce unnecessary referrals and enhance the efficiency of healthcare services.